New catalytic mechanism for human purine nucleoside phosphorylase - Canduri, F.; Fadel, V; Basso, L. A.; Palma, Mario Sergio [UNESP]; Santos, D. S.; de Azevedo, W. F. (Elsevier B.V., 2005)
Human purine nucleoside phosphorylase has been submitted to intensive structure-based design of inhibitors, most of them using low-resolution structures of human PNP. Recently, several structures of human PNP have been reported, which allowed redefinition of the active site and understanding of the structural basis for inhibition of PNP by acyclovir and immucillin-H. Based on previously solved human PNP structures, we proposed here a new catalytic mechanism for human PNP, which is supported by crystallographic studies and explains previously determined kinetic data. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: PNP; synchrotron radiation; Structure; drug design